2014
DOI: 10.1074/jbc.m114.556639
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylphosphatidylinositol Anchoring Directs the Assembly of Sup35NM Protein into Non-fibrillar, Membrane-bound Aggregates

Abstract: Background: Sup35NM is a soluble protein that when misfolded forms amyloid fibril aggregates. Results: When tethered to membranes via a lipid anchor, Sup35NM aggregates adopt a non-fibrillar, membrane-bound structure. Conclusion: Lipid anchor-directed membrane association prevents assembly into fibrils. Significance: This may explain differences between prion diseases compared with related protein aggregation diseases because only prion diseases involve aggregation of a lipid-anchored protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…The C-terminal green fluorescent protein (GFP) domain contains an A206K substitution to avoid dimerization of the fluorophore (65), which could promote aggregation of PrP by bringing two molecules into close proximity. GFP was added for imaging purposes; any aggregation of the TM PrP construct would result in clusters of GFP fluorescence, which could be observed in real time as seen with GPI-anchored Sup35NM (48,49). Furthermore, this domain serves to firmly anchor the TM PrP in the membrane such that it could not be removed without either proteolysis or severe compromise of the integrity of the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The C-terminal green fluorescent protein (GFP) domain contains an A206K substitution to avoid dimerization of the fluorophore (65), which could promote aggregation of PrP by bringing two molecules into close proximity. GFP was added for imaging purposes; any aggregation of the TM PrP construct would result in clusters of GFP fluorescence, which could be observed in real time as seen with GPI-anchored Sup35NM (48,49). Furthermore, this domain serves to firmly anchor the TM PrP in the membrane such that it could not be removed without either proteolysis or severe compromise of the integrity of the plasma membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The PrP res aggregates in the two inocula have different ultrastructures, with fibrils adopting an amyloid conformation and microsomebound aggregates adopting a nonfibrillar, apparently nonamyloid structure (7,35,44,49,(118)(119)(120)(121). Furthermore, PrP res in the two inocula might be expected to interact differently with distinct membrane regions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Interestingly, the experimental addition of a GPI anchor to the amyloidogenic yeast protein Sup35p appears to have an analogous biochemical influence, promoting the formation of non-fibrillar aggregates with ultrastructural similarity to PrP Sc . 25 Recent work has shown that anchorless PrP Sc more readily crosses a species barrier. 26 Finally, the co-expression of anchorless and wild-type PrP C molecules in recipient animals appears to allow for the detection of infectious activity in PrP amyloid fibril preparations.…”
Section: Influence Of Post-translational Modifications On Protein Folmentioning
confidence: 99%